Ragweed sublingual tablet immunotherapy: part 1 - evidence-based clinical efficacy and safety - Creticos, Peter Socrates; Pfaar, Oliver (Immunotherapy, 2018)
Sublingual tablet immunotherapy provides an attractive alternative approach to allergen immunotherapy, as the allergen is administered as a rapidly dissolving sublingual tablet. Part I of this two-part series on the ragweed sublingual tablet describes the dose-ranging clinical work, the safety studies and the clinical outcomes from the pivotal trials which provide clear evidence for statistically significant and clinically meaningful benefit in the treatment of patients suffering from ragweed-induced seasonal allergic rhinitis-conjunctivitis with or without milder asthma. The robust results observed in the clinical trials performed with the ragweed sublingual tablet are defined by the quality of their study design, their use of a standardized allergen extract, their consistent reproducibility in demonstrating therapeutic efficacy and their properly quantified and graded safety data.
Gesehen am 02.07.2019